Indonesian students’ motivation to pursue tertiary education in Japan - Umoro, Anisa Ledy (Universitas Dian Nuswantoro, 2023)
This paper aims to investigate the motivations of Indonesian students to pursue tertiary education in Japan. Investigating the experiences and perspectives of five Indonesian students, collected through in-dept interview, pursuing a degree program in Japan, this study argued that academic factors alone proved insufficient in capturing a comprehensive picture of students' motivation. The findings revealed that while academic motivation remained as an important driving force, socio-cultural factors contributed heavily to maintaining the students’ interest towards Japan. Interestingly, the findings also revealed that the students’ consideration to continue study in Japan was heavily influenced by routine and seemingly mundane matters namely, day-to-day living experience, such as the tolerance exhibited by Japanese society towards religious practices, the geographical proximity, and safety concerns, rather than being primarily driven by academic ambitions. Thus, to gain comprehensive students’ motivations in pursuing higher education abroad, it is necessary to contextualize it within a broader socio-cultural background.